Inferring the dark matter velocity anisotropy to the cluster edge. Issue 3 (23rd November 2020) - Svensmark, Jacob; Hansen, Steen H; Martizzi, Davide; Moore, Ben; Tessier, Romaine
ABSTRACT: Dark matter (DM) dominates the properties of large cosmological structures such as galaxy clusters, and the mass profiles of the DM have been inferred for these equilibrated structures for years by using cluster X-ray surface brightnesses and temperatures. A new method has been proposed, which should allow us to infer a dynamical property of the DM, namely the velocity anisotropy. For the gas, a similar velocity anisotropy is zero due to frequent collisions; however, the collisionless nature of DM allows it to be non-trivial. Numerical simulations have for years found non-zero and radially varying DM velocity anisotropies. Here we employ the method proposed by Hansen & Piffaretti, and developed by Høst et al. to infer the DM velocity anisotropy in the bright galaxy cluster Perseus, to near five times the radii previously obtained. We find the DM velocity anisotropy to be consistent with the results of numerical simulations, however, still with large error bars. At half the virial radius, we find the DM velocity anisotropy to be non-zero at 1.7$\, σ$, lending support to the collisionless nature of DM.